Utopian Thinking: Dworkin's Law's Empire Seen From a Utopian Perspective - Varangu, Anne M. (My University, 1992)
In this paper I argue that what we commonly understand as 'utopias' are but a particular kind of utopia. The inhibitions we have about spending our energy on useless dreams about perfect societies, either in some long ago time, some far away place, or in our own futures, stem from our familiarity with those utopias which can generally be described as being modelled after Plato.
There are elements of utopian thinking in many of our approaches to social problems. We do not recognize them for what they are because of their negative connotation. We are therefore unable to take advantage of the many positive features of utopian thought. Our efforts to avoid being labelled utopian have a negative effect on our lives.
Dworkin structures Law's Empire partly in response to his understanding of utopias. He too tries to disassociate himself from them and claims instead to be concerned with existing practice. There are, however, many utopian elements in Law's Empire. In not recognizing them as such we run the risk of forgetting to think about what we need to do in order to bridge the gap between who we are now and who we want to be.
Keywords: Philosophy; Philosophy